Kontroversi dan Dinamika Penentuan Wali Nikah: Kajian Sosiologis dan Yuridis - Alfaruq, Moh. Salman; komarudin, moh (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2025)
Marriage guardian is one of the pillars of marriage that influences the validity of the marriage. However, in practice, there is often a mismatch between the guardian who should be and the guardian who is present, which can result in legal and social problems. This study aims to identify the reasons why people refer marriage guardians to the penghulu and analyze their impact on Islamic family law. Through a juridical-sociological approach, this study uses a descriptive analytical method with data collection through interviews and observations. The results of the study show that people tend to ignore the position of the lineage guardian that has been regulated in Islamic law, turning to the penghulu as the marriage guardian. This phenomenon creates the impression that the lineage guardian is no longer considered sacred, thus affecting religious values in marriage. From a legal perspective, the determination of an inappropriate marriage guardian can have legal consequences, including the status of children from the marriage. This study recommends the need for socialization regarding the importance of understanding the position of the guardian in marriage and the urgency to return to the provisions of fiqh that have been set to maintain the validity and sanctity of marriage.